2011
DOI: 10.1108/09590551111104486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shopper attributes on retail format choice behaviour for food and grocery retailing in India

Abstract: PurposeRetailing in India is an unchartered territory. Food and grocery is the most promising area for setting up retail business in India. An understanding of shopper retail format choice behaviour will enable retailers to segment their market and target specific consumer groups with strategies premeditated to meet their retail needs. The purpose of this paper is to make a detailed study on the effect of shoppers' demographic, geographic and psychographic dimensions in terms of format choice behaviour in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(26 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…5;2016 processing industry has kept the organized chains basically non competitive and out of fray from the main marketing scene. Despite these road blocks, organized food retailing is expanding and making its presence felt in different pockets of the country (Prasad & Aryasri, 2011). Now some savvy customers are making a shift towards this format.…”
Section: Food Retail Format In Indiamentioning
confidence: 99%
“…5;2016 processing industry has kept the organized chains basically non competitive and out of fray from the main marketing scene. Despite these road blocks, organized food retailing is expanding and making its presence felt in different pockets of the country (Prasad & Aryasri, 2011). Now some savvy customers are making a shift towards this format.…”
Section: Food Retail Format In Indiamentioning
confidence: 99%
“…on consumer selection of retail shops [25][26][27][28][29][30][31][32]. In addition, several studies have used socio-economic factors such as academic background and income, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When choosing a shop, a consumer considers the facilities/services, environmental factors, accessibility, shop mood, salespersons, and their competencies, and so on, as their main factors. When there is a feeling of satisfaction with the experience, the consumer revisits the shop and may recommend it to acquaintances [29,[42][43][44][45][46][47][48][49]. Location factors are also important factors that affect consumer purchase behavior in Korean traditional retail districts [50].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, demographic factors alone do not fully explain retail practice or consumer choices and decisions. Thus, Prasad & Aryasri (2011) asserted that "Traditional demographic variables cannot identify the complete characteristics of an evolutionary retail market because consumers in the same demographic group have very different psychographic make-up". Martínez & Montaner (2008) observed that psychographic rather than the socio-demographic profiling of consumers better explains store brand proneness.…”
Section: Introductionmentioning
confidence: 99%
“…A study of shopper attributes and behaviour in the retail sector in India recognized that "shoppers' age, gender, occupation, education, monthly household income, family size and distance travelled to store have significant association with retail format choice decisions" (Prasad & Aryasri, 2011). The authors also asserted that demographic factors have important practical implications for food and grocery retailers, for creating better understanding of shopper behaviour, segmenting and targeting consumers and formulating of effective and competitive marketing strategies in the emerging Indian retail markets they studied.…”
Section: Introductionmentioning
confidence: 99%